Genes That Mediate Starch Metabolism in Developing and Germinated Barley Grain - Collins, Helen M.; Betts, Natalie S.; Dockter, Christoph; Berkowitz, Oliver; Braumann, Ilka; Cuesta-Seijo, Jose A.; Skadhauge, Birgitte; Whelan, James; Bulone, Vincent; Fincher, Geoffrey B. (Frontiers in Plant Science, 2021)
Starch is synthesized in the endosperm of developing barley grain, where it functions as the primary source of stored carbohydrate. In germinated grain these starch reserves are hydrolysed to small oligosaccharides and glucose, which are transported to the embryo to support the growth of the developing seedling. Some of the mobilized glucose is transiently stored as starch in the scutellum of germinated grain. These processes are crucial for early seedling vigour, which is a key determinant of crop productivity and global food security. Several starch synthases (SS), starch-branching enzymes (SBEs) and starch debranching enzymes (isoamylases, ISA), together with a limit dextrinase (LD), have been implicated in starch synthesis from nucleotide-sugar precursors. Starch synthesis occurs both in the developing endosperm and in the scutellum of germinated grain. For the complete depolymerization of starch to glucose, α-amylase (amy), β-amylase (Bmy), isoamylase (ISA), limit dextrinase and α-glucosidase are required. Most of these enzymes are encoded by gene families of up to ten or more members. Here RNA-seq transcription data from isolated tissues of intact developing and germinated barley grain have allowed us to identify the most important, specific gene family members for each of these processes in vivo and, at the same time, we have defined in detail the spatio-temporal coordination of gene expression in different tissues of the grain. A transcript dataset for 81,280 genes is publicly available as a resource for investigations into other cellular and biochemical processes that occur in the developing grain from six days after pollination.